Seroprevalence of Bordetella pertussis antibodies in Libyan pregnant women at the time of delivery - Suleiman Abusrewil; Mostafa Gawass; Inas Alhudiri; Marwan Sherif; Fawzi Ebrahim; Ali Amgadmi; Yosra Lamami; Salah Tabal; Musa O. Busarira; Hussain Asherkaci; Lubna Almaghur; Samira Al Dwigen; et al. (Vaccine: X)
Background: Pertussis is a highly contagious respiratory disease. Low levels of maternal antibodies make infants more susceptible to pertussis infection before they are eligible for vaccination at 2 months of age. This study aimed to investigate the seroprevalence of antibodies against Bordetella pertussis in Libyan pregnant women at the time of delivery. Methods: In this observational cross-sectional clinic-based study, 840 pregnant women were enrolled at five tertiary hospitals in three major cities in Libya from March 2023 to February 2024. Informed consent was obtained from all subjects involved in the study. At the time of delivery, venous blood was extracted from participants, and the samples were analyzed for serum levels of anti-B.pertussis toxin antibodies (IgG and IgA) using enzyme-linked immunosorbent assay (ELISA). Samples were positive if the antibody level was ≥100 IU/mL for IgG or ≥ 12 IU/mL for IgA. Results: Mean age of pregnant women was 31.1 ± 6.2 years old. All participants had received four doses of whole cell pertussis vaccine as part of the expanded Libyan national immunization program during their childhood. In this study, 827 (98.5 %) participants had IgG and IgA antibodies to B.pertussis toxin below the cut-off level of the assay. Only 13 (1.5 %) participants had recent infections (Two were positive for IgG, nine were positive for IgA antibodies and two were positive for both antibodies). Conclusions: In this study, most pregnant women in Libya were seronegative for B. pertussis antibodies. This makes their young infants more vulnerable to pertussis infection at this critical age. These findings support the need to introduce maternal Tdap vaccination as an important preventive strategy to reduce the burden of neonatal and younger infants' pertussis infections in Libya. National immunization programs should prioritize maternal vaccination, booster doses, and enhanced surveillance to protect the most vulnerable groups.